2005
DOI: 10.1080/00015550510033705
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Parathyroid Hormone and Parathyroid‐related Peptide in Psoriasis

Abstract: Psoriasis is a common skin disorder that may be triggered by hormonal disturbances, among other factors. Some studies have demonstrated an elevation of serum parathyroid hormone (PTH) levels in psoriasis and several other diseases of keratinization of unknown aetiology. PTH-related peptide (PTH-rp), on the other hand, is a potent inhibitor of epidermal cell growth factor and is not expressed in psoriatic skin. Serum levels of this peptide have not been reported in psoriasis. Immunoassay was used to measure ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Recent studies have shown that patients with psoriasis have an elevated serum level of PTH that correlates with PASI and is reduced upon treatment . Hyperparathyroidism has also been observed in other skin disorders characterized by keratinization .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have shown that patients with psoriasis have an elevated serum level of PTH that correlates with PASI and is reduced upon treatment . Hyperparathyroidism has also been observed in other skin disorders characterized by keratinization .…”
Section: Discussionmentioning
confidence: 99%
“…Hyperparathyroidism has also been observed in other skin disorders characterized by keratinization . Although the exact mechanism remains unclear, it has been postulated that loss of calcium through the skin in these conditions can stimulate PTH synthesis . Alternatively, hyperparathyroidism can be secondary to vit‐D deficiency status as observed in patients with psoriasis .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations